Barriers to Treatment and Control of Hypertension among Hypertensive Participants: A Community-Based Cross-sectional Mixed Method Study in Municipalities of Kathmandu, Nepal - Devkota, Surya; Dhungana, Raja Ram; Pandey, Achyut Raj; Bista, Bihungum; Panthi, Savyata; Thakur, Kartikesh Kumar; Gajurel, Ratna Mani (Frontiers in Cardiovascular Medicine, 2016)
Introduction Despite the established evidence on benefits of controlling raised blood pressure and development of several guidelines on detection and management of hypertension, people often have untreated or uncontrolled hypertension. In this context, we undertook this study to identify the barriers existing in hypertension treatment and control in the municipalities of Kathmandu district in Nepal. Methods This was a community based, cross-sectional mixed method study conducted in the municipalities of Kathmandu district in Nepal between January and July 2015. Among 587 randomly selected participants, the aware hypertensive participants were further assessed for the treatment and control of hypertension. For qualitative component, 20 participants having uncontrolled hypertension took part in two focused group discussions and two cardiac physicians participated in in-depth interviews. Results Out of 587 participants screened, 191 (32.5%) were identified as hypertensive. Among 191 hypertensive participants, 118 (61.8%) were aware of their problem. Of the 118 aware hypertensive participants, 93 (78.8%) were taking medicines, and among those treated, 46 (49.6%) had controlled hypertension. Proportions of participants taking anti-hypertensive medications varied significantly with age groups, ethnicity, occupation and income. Hypertension control was significantly associated with use of combination therapy, adherence to medication, follow-up care, counseling by health-care providers, and waiting time in hospital. Being worried that the medicine needs to be taken lifelong, perceived side effects of drugs, non-adherence to medication, lost to follow-up, inadequate counseling from physician, and lack of national guidelines for hypertension treatment were the most commonly cited barriers for treatment and control of hypertension in qualitative component of the research. Conclusion Large proportion of the hypertensive population has the untreated and the uncontrolled hypertension. Efforts to dispel and dismantle the myths and barriers related to hypertension treatment and control are warranted to reduce the consequences of uncontrolled hypertension.